Parents as chaperones the long distance study results for elementary school students - Margini (ETUDE: Journal of Educational Research, 2021)
Background: Student parents are supposed to provide maximum chaperones in primary school study. However, some parents are not at home at all and work late into the night, including the parents of Pasir Jawa 01. Purpose: The results of student study can be seen from parents' association. Therefore, the intent is to know the parent's relation to the students' learning during long distance study. Design and methods: The method used was the quantitative method, the collection of data done with Numbers and written documentation. The analysis subject is student parents and student learning during the long range learning process. Results: This study suggests that there is no or no influence between parent-teaching and student learning during long range study. This is because some of the student parents work late into the night so that the child feels inadequate to his or her parents' attention, when parents are not at home only a few students are accompanied by other family  members, a parent's education, parental understanding in operating the technology and the student's parent's cell phone monitoring policies that cause a parent's absence from the results of a student's learning over long distances.